Synthesis, reactions and biological evaluation of some novel thienothiophene derivatives - Mohamed, Mounir Abbas Ali; Salah, Hanan; El-Saghier, Ahmed Mohamed Mohamed (European Journal of Chemistry, 2019)
Synthesis of some new bis(chalcones)-based thienothiophene derivatives and study of their synthetic utilities as building blocks for new bis(thiazole), bis(dihydropyran), bis(dihydro pyridine), bis(isoxazoles), bis(pyrazoles), bis(hydropyrimidinethiones), bis(tetrahydro diazepines, oxazepines) and bis(dihydrobenzodiazepnies, benzoxazepines) each linked to a thienothiophene core, is reported. Biological evaluation of the obtained compounds as antibacterial agents was achieved. Compounds 4b, 4c, 7a, 6a, 9a and 11b were found to be very potent against P. aeruginosa, E. coli and K. pneumonia.